Freedom's debtors : British antislavery in Sierra Leone in the age of revolution - Scanlan, Padraic X. (Yale University Press : Yale University Press, 2017)
A history of the abolition of the British slave trade in Sierra Leone and how the British used its success to justify colonialism in Africa.
Keywords: Antislavery movements -- Sierra Leone -- History.; Slavery -- Sierra Leone -- History.; Mouvements antiesclavagistes -- Sierra Leone -- Histoire.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Antislavery movements; Slavery; Sierra Leone; History